Penilaian Berbasis Kelas untuk Meningkatkan Prestasi Belajar pada Materi Persilangan - Nurhidayah Nurhidayah (SAP (Susunan Artikel Pendidikan), 2021)
This study aims at improving the understanding of crossbreeding concepts through class-based assessment methods at SMP Negeri 131 Jakarta. Classroom action research was conducted in 2 cycles (I and II) from July to October 2019 with stages of planning, implementation and reflection. Data analysis and discussion were carried out using quantitative and qualitative techniques by observing the improvement in each cycle. The ability measuring instruments were LKPD and multiple choice written tests. The attitude measuring instruments during the learning process were interviews and observation sheets. The result showed an increase in competence of students' understanding in crossbreeding concept which was initially under the KKM (80), and tended to increase from 80.83 to 86.11. In the attitude aspect, there was a positive response in accepting learning, the classroom was quite active and participatory. It can be concluded that the class-based assessment method is effective in increasing the understanding of students in crossbreeding concepts, as well as improving students’ attitudes during the learning process. The implication of this study is the positive attitude, classroom situation is related with the teachers’ teaching ability so teachers become challenged to improve. This study is also a reference for colleagues in developing class-based learning.